2016
DOI: 10.1007/s10157-016-1282-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods of steroid administration combined with tonsillectomy for IgA nephropathy patients

Abstract: In IgAN patients, treatment of group 3A may be effective for inducing rapid remission of hematuria. Further studies are needed to establish an appropriate protocol for TSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The study indicated that the addition of mizoribine might reduce the required number of courses of corticosteroid pulse therapy. Watanabe et al [ 27 ] showed that TSP3 had an effect to rapidly induce remission of hematuria compared to TSP1, although there was no significant difference in the clinical remission rates between the 2 groups, which was consistent with our study. Their study was conducted over a short term and did not assess renal outcome.…”
Section: Discussionsupporting
confidence: 92%
“…The study indicated that the addition of mizoribine might reduce the required number of courses of corticosteroid pulse therapy. Watanabe et al [ 27 ] showed that TSP3 had an effect to rapidly induce remission of hematuria compared to TSP1, although there was no significant difference in the clinical remission rates between the 2 groups, which was consistent with our study. Their study was conducted over a short term and did not assess renal outcome.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of IgAN shows marked differences across different ethnic groups, being more prevalent in people with East Asian ancestry and less prevalent in people with African ancestry compared with Caucasians 2 . In addition, differences in the clinical features of IgAN in Caucasian compared with Chinese patients have been recognized for a long time 3 , most notably the clear male preponderance of IgAN in Caucasian studies of IgAN that is absent (or even reversed) in East Asian populations, suggesting that important and incompletely understood differences in disease pathophysiology exist across different populations [4][5][6][7][8] . Recent work has identified a number of genetic factors, mostly associated with mechanisms of defense against infection, that are associated with altered risk of disease [9][10][11] , and although the prevalence of the known genetic factors vary across different ethnic groups, the observed differences fall some way short of explaining the differences in prevalence of the disease in different regions 2,12 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, no study has been reported on the comparison of the clinical course between the two SP protocols. However, there are several studies on the number of sessions of SP therapy, and three session of SP therapy were reported to have a higher remission rate of urinary findings than did one or two sessions of SP therapy [ 23 ]. Considering the nature of SP therapy, as the dose of steroids administered in the first month is high in the CSP group, earlier remission of proteinuria would be obtained in this group than in the ISP group.…”
Section: Discussionmentioning
confidence: 99%
“…When choosing SP therapy, the adverse effects and length of hospitalization should be considered. Since the adverse effects of steroid therapy have been shown in several previous reports, they have been recognized as profound issues [ 15 , 23 ]. As expected, these previous studies have reported that SP therapy led to the amelioration of urinary findings and slowing down the progression of kidney dysfunction; however, it also significantly increased the risk for adverse events [ 10 , 21 ].…”
Section: Discussionmentioning
confidence: 99%